2009
DOI: 10.1080/15299710802660029
|View full text |Cite
|
Sign up to set email alerts
|

Bisexuals “Doing Gender” in Romantic Relationships

Abstract: Employing the concept of gender as a situated performance, this research explores negotiations of gender performances by bisexuals in interper-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…This is likely due to a mix of genders of the participants’ romantic partners, which has been shown to affect the internalized beauty ideal in BIW (87). A previous study found that BIW with a male partner showed a more traditional feminine body ideal, while BIW with a female partner had a less strictly defined body ideal (88). Accordingly, the gender of the current partner may have led to different body image ideals among the BIW, which in turn may have resulted in the intermediate position of BIW between the two other groups.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to a mix of genders of the participants’ romantic partners, which has been shown to affect the internalized beauty ideal in BIW (87). A previous study found that BIW with a male partner showed a more traditional feminine body ideal, while BIW with a female partner had a less strictly defined body ideal (88). Accordingly, the gender of the current partner may have led to different body image ideals among the BIW, which in turn may have resulted in the intermediate position of BIW between the two other groups.…”
Section: Discussionmentioning
confidence: 99%
“…All of my respondents spoke extensively about the ways in which intense communication between those in the relationship helped foster their experience as open and honest in their identity as bisexual and in their polyamorous relationships. Pennington (2009) questions bisexual self-awareness and bisexuals' ability to critique hegemonic norms based on their experience of being outside hegemonically defined institutions. Of her research she states, "The bisexuals in this research are significantly self-aware of their ideas about sex/gender, and some proffer extensive critiques of hegemonic norms.…”
Section: A R Mossmentioning
confidence: 99%
“…There are, in fact, compelling parallel findings from these two non-heteronormative groups. Pennington's (2009) interview study of bisexuals found that many of these individuals were "critically aware of dominant conceptualizations of sex/gender as social structures of power" (p. 45), similar to the perceptions of the transgender individuals interviewed by Green (2005). Similar to the ideas of Monro's (2000) transgender theory, Pennington's respondents noted how their own lived experiences did not correspond with traditional notions of gender.…”
Section: The Intersectionality Of Gender and Sexual Identitiesmentioning
confidence: 65%